The Family Jensen: The Violent Land - Book 3 Violent land - Johnstone, William W.; Johnstone, J.A. (New York : Kensington Pub., 2012)
"They are strangers in a strange land-a band of German immigrants trespassing across the Jensen family spread. Led by a baron fleeing a dark past in Germany and accompanied by a woman beautiful enough to dazzle young Matt, the pilgrims are being pursued by a pack of brutal outlaws hungry for blood, money-or maybe something else ... The Jensens are willing to help the pioneers get to the promised land in Wyoming. But they dont know the whole story of their newfound friends, or who the outlaws really are. By the time the wagon train reaches Wyoming the truth is ready to explode-in a clash of hard fighting, hard choices, and hard deaths in a violent land" -- Cover verso.
"Pinnacle western"--Spine.
Keywords: Jensen, Smoke (Fictitious character) -- Fiction; Immigrants -- Fiction; Wyoming -- Fiction; Western fiction